Review of the Novel Investigational Antifungal Olorofim - Wiederhold, Nathan P. (J Fungi (Basel), 2020)
The incidence of invasive fungal infections caused by molds and endemic fungi is increasing. There is also concern regarding increased rates of reduced susceptibility or frank resistance among Aspergillus and Coccidioides species, while Scedosporium species, Lomentospora prolificans, and Fusarium species are inherently less susceptible or intrinsically resistant to clinically available antifungals. Olorofim (formerly F901318) is the first member of the orotomide class of antifungals to be evaluated clinically for the treatment of invasive mold infections. This agent inhibits dihydroorotate dehydrogenase, a key enzyme in the biosynthesis of pyrimidines. Olorofim has activity against many molds and thermally dimorphic fungi, including species that are resistant to azoles and amphotericin B, but lacks activity against yeasts and the Mucorales. It is currently being developed for both oral and intravenous administration. Although published clinical outcome data have been limited to case reports to date, the results against invasive and refractory infections are promising. This review describes the mechanism of action of olorofim, its in vitro spectrum of activity, and what is currently known about its pharmacokinetic profile and clinical efficacy.